Identification of Genes and MicroRNAs Affecting Pre-harvest Sprouting in Rice (Oryza sativa L.) by Transcriptome and Small RNAome Analyses - Park, Minsu; Choi, Woochang; Shin, Sang-Yoon; Moon, Hongman; Lee, Dowhan; Gho, Yun-Shil; Jung, Ki-Hong; Jeon, Jong-Seong; Shin, Chanseok (Frontiers in Plant Science, 2021)
Pre-harvest sprouting (PHS) is one of the primary problems associated with seed dormancy in rice (Oryza sativa L.). It causes yield loss and reduces grain quality under unpredictable humid conditions at the ripening stage, thus affecting the economic value of the rice crop. To resolve this issue, understanding the molecular mechanism underlying seed dormancy in rice is important. Recent studies have shown that seed dormancy is affected by a large number of genes associated with plant hormone regulation. However, understanding regarding the effect of heat stress on seed dormancy and plant hormones is limited. This study compared the transcriptome and small RNAome of the seed embryo and endosperm of two contrasting japonica rice accessions, PHS susceptible (with low seed dormancy) and PHS resistant (with high seed dormancy), at three different maturation stages. We found that 9,068 genes and 35 microRNAs (miRNAs) were differentially expressed in the embryo, whereas 360 genes were differentially expressed in the endosperm. Furthermore, we identified and verified the candidate genes associated with seed dormancy and heat stress-related responses in rice using quantitative real-time PCR. We newly discovered eight hormone-related genes, four heat shock protein-related genes, and two miRNAs potentially involved in PHS. These findings provide a strong foundation for understanding the dynamics of transcriptome and small RNAome of hormone- and heat stress-related genes, which affect PHS during seed maturation.